School dynamics associated to the construction of an intercultural curriculum for peace and territorial justice in the Colombian Caribbean, 2018-2019 - González Monroy, Luis Alfredo; Ortiz Segrera, Jennyfer Tatiana; Gamarra Rosado, Luis David (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article has to do with a research carried out between 2018 and 2019 in a school of a rural setting in the Caribbean, which suffered the attacks of the Colombian fratricidal conflict. This region is characterized by its agricultural vocation of  banana crops for export. In this context, appears the primary school Thelma Rosa de Arévalo as a forum in which social phenomena are manifested, which the school institution begins to lead through transformation processes, using the action research methodology using the cooperative action research(-IAC) methodology. To do this, it makes a strategic alliance with the Educational Quality in a Plural World-CEMPLU group, attached to the Universidad del Magdalena. The epistemological process faithfully examined the school dynamics of a peasant community, associated with the construction of an intercultural curriculum that promotes territorial peace and justice. To do this, it was necessary to qualify the co-researcher teachers in the episteme "interculturality" as the central axis of the study. Their experiences and knowledge were taken into account to value their teaching expertise and understanding their sufferings as victims. In the latter aspect, the accumulated pain did not allow, in the first turn of the methodological spiral, the proposed teleological transformation will be achieved. The proposed teleological transformation will be achieved, suggesting to the writing of this text, to make a second turn of the IAC loop. Among the results it was found that the Institutional Educational Project-PEI is a technical document but it does not reflect the local reality avoiding the growth of an intercultural curriculum, since the latter requires the local educational communities and its members they should know "themselves". Without this elemental knowledge the imprint that marks the identity of people and their communities cannot be understood.